Carrier Performance Evaluation at PT. XYZ Based on Vendor Performance Indicator (VPI) with the Analytical Hierarchy Process (AHP) Method - Rizky Khairani; Jessica Olifia (Politeknik Negeri Batam, 2025)
XYZ is a manufacturing company in the household electronic appliance industry that collaborates with several carrier vendors to support smooth goods delivery. These carriers include CMA, MAERSK, COSCO, HMM, and SEALAND ASIA. The problem occurring in PT. XYZ's shipping process is that some containers owned by the carriers do not meet the quality standards used by the company. This study aims to determine the performance of carriers used by PT. XYZ and the criteria used in evaluating carrier performance based on the Vendor Performance Indicators (VPI) framework, which includes Quality, Cost, Delivery, Flexibility, and Responsiveness (QCDFR), using the Analytical Hierarchy Process (AHP) method. This type of research is descriptive quantitative research. The research data was obtained from questionnaire responses from 5 experts in the SCM Shipping department of PT. XYZ. The results of this study indicate that the most influential criterion in evaluating carrier performance is quality, with a weight of 0.424, while the least influential criterion is cost, with a weight of 0.048. The carrier with the best performance is CMA, with a weight of 0.953, while the carrier with the lowest performance is SEALAND ASIA, with a weight of 0.535.